About the Journal - Naknuan, Natthakarn (FOYER: The Journal of Humanities, Social Sciences, and Education, 2024)
FOYER: The Journal of Humanities, Social Sciences, and Education a publication of Faculty of Liberal Arts, Mahidol University, was first published in 2024. Two semi-annual issues are scheduled for January-June and July-December each year. FOYER: The Journal of Humanities, Social Sciences, and Education publishes articles in Thai, English, and also other languages. The editor welcomes submissions of previously unpublished manuscripts in four categories: academic -, research -, review articles, and book reviews. Submitted manuscripts will be screened through a double-blind review by three readers from relevant academic disciplines. FOYER: The Journal of Humanities, Social Sciences, and Education welcomes submissions of previously unpublished manuscripts in four categories: academic -, research -, review articles, and book reviews. Submitted manuscripts may not currently be reviewed for other journals. A complete version of articles appearing in conference proceedings may be considered, provided that the author(s) has extended the original by 60% at the least. In this case, an explicit acknowledgment of the first publishing is required in the extended manuscript.